Biogas upgrading towards acetic acid production using Clostridium thailandense supplemented with granular activated carbon (GAC) and L-arginine: A genomic analysis approach - Srisuda Chaikitkaew; Nantharat Wongfaed; Chonticha Mamimin; Sompong O-Thong; Alissara Reungsang (Carbon Resources Conversion)
This study explores the impact of granular activated carbon (GAC) and L-arginine supplementation on biogas upgrading and acetic acid production employing Clostridium thailandense. GAC and L-arginine concentrations ranged from 0 to 20 g/L and 0 to 5 g/L, respectively, with H2 acting as the electron donor at an H2 to CO2 ratio of 2:1 (v/v). Experiments were conducted at 30 °C with an agitation speed of 150 rpm. Additionally, gene annotation of the C. thailandense genome using Rapid Annotations using Subsystems Technology (RAST) identified genes involved in CO2 to acetic acid conversion. Results indicate that adding 7.5 g/L GAC boosts CH4 purity in biogas, elevating CO2 and H2 consumption efficiencies to 88.3 % and 98.7 %, respectively. This enhancement leads to a CH4 content increase to 93.3 %, accompanied by 0.90 g/L acetic acid production. Conversely, L-arginine demonstrates no significant impact on CO2 conversion. Leveraging RAST, the study identifies hydrogenase genes and NADH-dependent ferredoxin-NADP+ oxidoreductase (Nfn), as crucial for heightened H2 consumption efficiencies and cell growth facilitated by GAC, thus enhancing biogas upgrading efficiency in C. thailandense. This research provides vital insights into optimizing sustainable biogas production through strategic GAC utilization and elucidates the roles of hydrogenase genes and Nfn.